Protocol for the derivation and culture of murine trophoblast organoids for CRISPR-Cas9 screening - Qian Mao; Jingwei Jiang; Qinying Ye; Haopeng Wang; Chao-Po Lin (STAR Protocols)
Summary: Murine trophoblast organoids present a more balanced array of trophoblast subtypes, rendering them a suitable platform for CRISPR-Cas9-based screening. Here, we present a protocol for the derivation and culture of murine trophoblast organoids from trophoblast stem cells or placentae. We describe steps for establishing and differentiating murine trophoblast organoids, the characterization of trophoblast organoids in both conditions, the generation of focused single guide RNA (sgRNA) libraries, and the subsequent screening using those libraries in murine trophoblast organoids.For complete details on the use and execution of this protocol, please refer to Mao et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.